Improving the Welfare of MSME Trader Families Through the Use of E-commerce - Sopian (International Journal of Integrated Science and Technology, 2024)
Even if e-commerce has a huge potential to improve the welfare of MSMEs, its execution is not always flawless. Some MSMEs can still have trouble using technology due to a lack of knowledge about digital platforms and a shortage of information technology-savvy personnel. This is the reason why e-commerce and its potential to enhance the well-being of MSME trade families are of interest to scholars. The purpose of this study is to ascertain how E-commerce usage affects MSME traders' families' well-being. This study employs a quantitative descriptive methodology, utilizing questionnaire distribution and library data gathering approaches. This study use basic linear regression data analysis approaches to sample 46 MSME traders in the Tugu Utara Subdistrict area of North Jakarta. The study's findings indicate that using e-commerce can help MSME traders in North Jakarta's Tugu Utara Subdistrict raise their family income to a somewhat satisfactory degree. It is intended that this study's findings will aid in future investigations.